METODOLOGÍA DE LAS ENCUESTAS TELEFONICAS - Agudelo, Gabriel; Ruiz Restrepo, Jaime; Aigneren, Miguel (La Sociología en sus Escenarios, 2010)
Abstract. The telephone survey of recent introduction in Colombia show to a substantive advantage with respect to the actual surveys or by costs and saving of time and access an up-to-date information as the telephone interviews are developed. Nevertheless, parallel to these evident advantages arises the problem from the representativeness of the given information the distortion that can be given with the distribution of the obtained calls: in the homes to minors or people generally respond who do not represent the home (qualified interviewer); also there are serious problems with the perception of insecurity in the high layers what makes difficult the obtaining of reliable and valid information. This last problem has become a serious obstacle for this type of methodology. Resumen. Los sondeos telefónicos de reciente introducción en Colombia muestran una ventaja sustantiva respecto a las encuestas presenciales ya sea por costos y ahorro de tiempo y acceso a una información actualizada a medida que se desarrollan las entrevistas telefónicas. Sin embargo, paralelo a estas evidentes ventajas surge el problema de la representatividad de la información dado la distorsión que se puede dar con la distribución de las llamadas logradas: generalmente en los hogares responden menores o personas que no representan el hogar (no son respondientes calificados); también hay serios problemas con la percepción de inseguridad en los estratos altos lo que dificulta la obtención de información confiable y válida. Este último problema se ha convertido en un serio obstáculo para este tipo de metodología.